A method of making a needle-punched, stitched structure quartz fiber reinforced quartz composite
Patent Information
- Application Number
- CN202611388177.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]现有工艺制备的石英纤维增强石英复合材料内部、表面存在较多气孔,导致了该材料的力、热、电综合性能离散较大,致使产品在加工壁厚相同的情况下,材料各区域的密度并不一定相同,造成产品壁厚理论上的差异,从而导致不同区域的介电性能存在差异,影响产品透波性能
1.本发明制得的石英纤维增强石英复合材料,密度为1.67-1.70g/cm3;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic matrix composite technology, and specifically relates to a method for preparing needle-stitched quartz fiber reinforced quartz composite materials. Background Technology
[0002] In recent decades, the development of wave-transparent materials has been rapid. Among the many candidate materials, quartz ceramic wave-transparent materials and quartz fiber reinforced ceramic wave-transparent materials have excellent comprehensive mechanical, thermal, and electrical properties. Quartz ceramic wave-transparent materials have a high market share and a strong foundation. However, in recent years, with the development trend of weaponry and equipment, the performance limitations of quartz ceramic wave-transparent materials have become increasingly apparent, and market demand is gradually decreasing. At the same time, with the gradual increase in domestic customers' requirements for product thermal shock resistance and reliability, the market growth of quartz fiber reinforced quartz composite materials is relatively fast. Therefore, it is of great significance to provide a method for preparing uniformity of needle-stitched quartz fiber reinforced quartz composite materials.
[0003] The existing process produces quartz fiber reinforced quartz composites with numerous pores on the inside and surface, resulting in significant dispersion in the material's overall mechanical, thermal, and electrical properties. Consequently, even with the same wall thickness, the density of different regions of the material may not be the same, leading to theoretical differences in the product's wall thickness. This, in turn, results in differences in the dielectric properties of different regions, affecting the product's wave transmission performance.
[0004] Therefore, providing a method for preparing needle-stitched structure-adaptive fiber-reinforced quartz composite materials that makes the product dense and uniform, improves the product strength, and ensures wave transmission is a technical problem that urgently needs to be solved in the existing technology. Summary of the Invention
[0005] To address the technical problems existing in the prior art, this invention provides a method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material, achieving overall product density and uniformity, high strength, and excellent wave transmission performance.
[0006] This invention employs a unique centrifugal impregnation method in the state of quartz fiber fabric. The impregnation solution is changed from pure silica sol to quartz ceramic slurry with a higher solid content. In the initial stage, the volume voids of the fiber fabric are filled. Subsequently, pure silica sol with smaller particle size and lower viscosity is used for impregnation to fill the fine voids, resulting in a more uniform product density and fewer internal defects.
[0007] To address the aforementioned technical problems, the present invention adopts the following technical solution: A method for preparing needle-punched and stitched structure-adaptive fiber-reinforced quartz composite materials includes fabric pretreatment, centrifugal sizing, preparation of quartz fiber preforms, and preparation of finished products, as detailed below: 1. Fabric pretreatment The quartz fiber fabric is cleaned with a 10-12 wt% hydrochloric acid solution, ensuring complete immersion. The primary purpose is to remove residual metal ions from the needle-punching process. After cleaning, deionized water is used to replace the acid ions. Once the pH of the washing solution is neutral, the fabric is dried at 120-180℃ to constant weight. Following drying, the fabric is pre-fired by increasing the temperature at a rate of 20-40℃ / h to 250-255℃ and holding for 1-3 hours, then increasing the temperature at a rate of 30-50℃ / h to 450-460℃ and holding for 1-3 hours. The temperature is raised to 550-560℃ at a rate of 40-60℃ / h and held for 1-3 hours to remove the organic impregnating agent from the fabric. Then, the fabric is placed in a firing furnace, and the temperature is raised to 345-355℃ at a rate of 50-80℃ / h and held for 0.5-3 hours. The temperature is then raised to 445-455℃ at a rate of 80-100℃ / h and held for 1-3 hours. The temperature is then raised to 515-525℃ at a rate of 120-150℃ / h and held for 2-4 hours. After cooling, a quartz fiber braid is obtained. The quartz fiber fabric has an areal density of 305-325 g / m³. 2 Its volume fraction is 42-45%.
[0008] 2. Centrifugal impregnation Quartz powder and silica sol were mixed at a mass ratio of 1:1.2-1.8, ball-milled for 60-96 hours at a speed of 35-45 r / min and a ball-to-material ratio of 1:2.1-2.3 to obtain a slurry with a viscosity of <300 mPa·S. The quartz powder has a particle size of 1200-1300 mesh; The silica sol has a solid content of 10-15%. The quartz fiber braid is fixed in a centrifuge. The slurry is added to the centrifuge, with the slurry level 20-25 cm above the quartz fiber braid. The centrifuge speed is adjusted to 350-500 rpm, and the mixture is centrifuged for 30-60 minutes. The mixture is then removed and placed in an oven at 180-185℃ to dry for 12-20 hours. After cooling, the heating rate is controlled at 60-90℃ / h, and the temperature is raised to 445-455℃. The temperature is held for 1-3 hours, and then the heating rate is controlled at 100-150℃ / h, and the temperature is raised to 640-660℃. The temperature is held for 0.5-2 hours, and then cooled to obtain a quartz fiber reinforced quartz composite preform.
[0009] 3. Preparation of quartz fiber preforms The quartz fiber reinforced quartz composite preform is placed upright in a vacuum mold and evacuated at -0.085 to -0.098 MPa for 2-5 hours to remove residual gas inside the quartz fiber fabric. The small impregnation channels of the preform are then opened, and the pressure is adjusted to -0.015 to -0.035 MPa. Low vacuum is applied slowly to facilitate the slow removal of gas from the quartz fiber preform. Silica sol with a solid content of 45-60 wt% is then introduced until the liquid level is 20-25 cm above the quartz fiber reinforced quartz composite preform. The pressure is maintained for 3-5 hours, and the preform is dried in an oven at 150-180℃ to constant weight. After cooling, a first-impregnation preform is obtained. The first-impregnated preform is placed upright in a vacuum mold and evacuated at -0.085 to -0.098 MPa for 3-5 hours. The pressure is then adjusted to -0.050 to -0.075 MPa to increase the vacuum force, which facilitates the removal of residual gas from the quartz fiber fabric preform. Silica sol with a solid content of 25-40 wt% is then introduced until the liquid level is 20-25 cm above the fiber fabric preform. The pressure is maintained for 2-4 hours. The preform is then removed and placed in an oven at 180-185℃ to dry to constant weight. After cooling, the second-impregnated preform is obtained. The preform with secondary impregnation is placed in a firing furnace. The heating rate is controlled at 50-80℃ / h, and the temperature is raised to 345-355℃. The temperature is held for 1-4 hours. The heating rate is controlled at 80-120℃ / h, and the temperature is raised to 445-455℃. The temperature is held for 1-3 hours. The heating rate is controlled at 120-150℃ / h, and the temperature is raised to 795-805℃. The temperature is held for 2-4 hours. After cooling, a quartz fiber preform is obtained.
[0010] 4. Preparation of finished product Quartz fiber blanks are processed into products according to requirements. The products are then vacuum impregnated by drawing a vacuum to -0.085 to -0.098 MPa and holding it for 2-5 hours. Silica sol with a solid content of 10-15 wt% is then drawn in. The low solid content and small particle size of the silica sol are beneficial for filling small pores and defects in the product. The impregnation continues until the liquid level is 20-25 cm above the product. The pressure is maintained for 2-4 hours. The product is then removed and placed in an oven at 180-185℃ to dry to constant weight. The vacuum impregnation process is repeated 2-4 times. After vacuum impregnation, the temperature is raised to 400-410℃ at a controlled heating rate of 80-120℃ / h and held for 1-3 hours. The temperature is then raised to 515-525℃ at a controlled heating rate of 100-150℃ / h and held for 1-3 hours. Finally, the product is cooled to obtain a quartz fiber reinforced quartz composite material.
[0011] This invention involves pre-firing quartz fiber fabric to obtain a quartz fiber braid, centrifugally impregnating the quartz fiber braid to densify the core layer region of the fiber fabric, drying it, vacuum impregnating it with a first silica sol impregnation solution to densify the outer region of the core layer, drying it, vacuum impregnating it with a second silica sol impregnation solution to densify the outer layer region of the fiber fabric, drying it, and then heat-treating it to obtain a quartz fiber reinforced quartz composite material blank. The quartz fiber reinforced quartz composite material preform is then processed into a shaped product, vacuum impregnated with a third silica sol impregnation solution to densify the small pores of the product, and the impregnation is repeated 2-4 times to achieve uniform densification of the entire product.
[0012] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The quartz fiber reinforced quartz composite material obtained by this invention has a density of 1.67-1.70 g / cm³. 3 ; 2. The quartz fiber reinforced quartz composite material obtained by the present invention has a tensile strength of 37-45 MPa, a flexural strength of 62-73 MPa, and a compressive strength of 79-92 MPa; 3. The quartz fiber reinforced quartz composite material obtained by the present invention has a dielectric constant of 2.76-2.84 and a loss tangent of 0.003-0.006. Detailed Implementation
[0013] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.
[0014] Example 1 1. Fabric pretreatment Quartz fiber fabric was cleaned with a 10wt% hydrochloric acid solution. After cleaning, deionized water was used to replace the acid radicals. Once the pH of the washing solution was neutral, it was dried at 150℃ to constant weight. After drying, it was pre-fired by heating at a rate of 30℃ / h to 253℃ and holding for 2 hours, then heating at a rate of 40℃ / h to 455℃ and holding for 2 hours, and then heating at a rate of 50℃ / h to 555℃ and holding for 2 hours. Then it was placed in a firing furnace and heated at a rate of 70℃ / h to 350℃ and holding for 2 hours, then heated at a rate of 90℃ / h to 450℃ and holding for 2 hours, and then heated at a rate of 135℃ / h to 520℃ and holding for 3 hours. After cooling, quartz fiber braid was obtained. The quartz fiber fabric has an areal density of 315 g / m³. 2 The volume fraction is 43%.
[0015] 2. Centrifugal impregnation Quartz powder and silica sol were mixed at a mass ratio of 1:1.5 and ball-milled for 75 hours at a ball milling speed of 40 r / min and a ball-to-material ratio of 1:2.2 to obtain a slurry with a viscosity of <300 mPa·S. The quartz powder has a particle size of 1250 mesh. The silica sol has a solid content of 12%. Quartz fiber braids were fixed in a centrifuge. Slurry was added to the centrifuge, with the slurry level 23 cm above the quartz fiber braids. The centrifuge speed was adjusted to 450 rpm, and the mixture was centrifuged for 45 minutes. The mixture was then removed and placed in an oven at 183℃ for 15 hours to dry. After cooling, the heating rate was controlled at 70℃ / h to raise the temperature to 450℃ and hold for 2 hours. The heating rate was then controlled at 120℃ / h to raise the temperature to 650℃ and hold for 1.5 hours. After cooling, a quartz fiber reinforced quartz composite preform was obtained.
[0016] 3. Preparation of quartz fiber preforms The quartz fiber reinforced quartz composite preform was placed upright in a vacuum mold and evacuated to -0.090 MPa for 3 hours. Then the pressure was adjusted to 0.020 MPa, and silica sol with a solid content of 50 wt% was drawn in until the liquid level was 23 cm above the quartz fiber reinforced quartz composite preform. The pressure was maintained for 4 hours, and the preform was dried in an oven at 165℃ to constant weight. After cooling, a first-impregnation preform was obtained. The first impregnation preform was placed upright in a vacuum mold and vacuumed at -0.092 MPa for 4 hours. The pressure was then adjusted to 0.035 MPa, and silica sol with a solid content of 35 wt% was drawn in until the liquid level was 23 cm above the fiber fabric preform. The pressure was maintained for 3 hours. The preform was then removed and placed in an oven at 183°C to dry to constant weight. After cooling, the second impregnation preform was obtained. The preform with secondary impregnation was placed in a firing furnace, and the heating rate was controlled at 70℃ / h to raise the temperature to 350℃ and hold for 3h. The heating rate was then controlled at 100℃ / h to raise the temperature to 450℃ and hold for 2h. Finally, the heating rate was controlled at 130℃ / h to raise the temperature to 800℃ and hold for 3h. After cooling, a quartz fiber preform was obtained.
[0017] 4. Preparation of finished product Quartz fiber blanks are processed into products according to requirements. The products are then vacuum impregnated by drawing a vacuum to -0.092 MPa and holding it for 3 hours. Silica sol with a solid content of 13 wt% is then drawn in until the liquid level is 23 cm above the product. The pressure is maintained for 3 hours. The product is then removed and placed in an oven at 183℃ to dry to constant weight. The vacuum impregnation process is repeated 3 times. After vacuum impregnation, the temperature is raised to 405℃ at a controlled heating rate of 100℃ / h and held for 2 hours. The temperature is then raised to 520℃ at a controlled heating rate of 120℃ / h and held for 2 hours. Finally, the product is cooled to obtain quartz fiber reinforced quartz composite material.
[0018] Example 2 1. Fabric pretreatment Quartz fiber fabric was cleaned with a 12wt% hydrochloric acid solution. After cleaning, deionized water was used to replace the acid radicals. Once the pH of the washing solution was neutral, it was dried at 180℃ to constant weight. After drying, it was pre-fired by heating at a rate of 40℃ / h to 255℃ and holding for 3 hours, then heating at a rate of 50℃ / h to 460℃ and holding for 3 hours, then heating at a rate of 60℃ / h to 560℃ and holding for 3 hours. Then it was placed in a firing furnace and heated at a rate of 80℃ / h to 355℃ and holding for 3 hours, then heating at a rate of 100℃ / h to 455℃ and holding for 3 hours, then heating at a rate of 150℃ / h to 525℃ and holding for 4 hours. After cooling, quartz fiber braid was obtained. The quartz fiber fabric has an areal density of 325 g / m³. 2 The volume fraction is 45%.
[0019] 2. Centrifugal impregnation Quartz powder and silica sol were mixed at a mass ratio of 1:1.8 and ball-milled for 96 hours at a ball milling speed of 45 r / min and a ball-to-material ratio of 1:2.3 to obtain a slurry with a viscosity of <300 mPa·S. The quartz powder has a particle size of 1300 mesh. The silica sol has a solid content of 15%. Quartz fiber braids were fixed in a centrifuge. Slurry was added to the centrifuge, with the slurry level 25 cm above the quartz fiber braids. The centrifuge speed was adjusted to 500 rpm, and the mixture was centrifuged for 60 minutes. The mixture was then removed and placed in an oven at 185℃ for 20 hours to dry. After cooling, the heating rate was controlled at 90℃ / h to raise the temperature to 455℃ and hold for 3 hours. The heating rate was then controlled at 150℃ / h to raise the temperature to 640℃ and hold for 2 hours. After cooling, a quartz fiber reinforced quartz composite preform was obtained.
[0020] 3. Preparation of quartz fiber preforms The quartz fiber reinforced quartz composite preform was placed upright in a vacuum mold and evacuated to -0.098 MPa for 5 hours. Then the pressure was adjusted to 0.035 MPa, and silica sol with a solid content of 60 wt% was drawn in until the liquid level was 25 cm above the quartz fiber reinforced quartz composite preform. The pressure was maintained for 5 hours, and the preform was dried in an oven at 180°C to constant weight. After cooling, a first-impregnation preform was obtained. The first impregnated preform was placed upright in a vacuum mold and evacuated to -0.098 MPa for 5 hours. The pressure was then adjusted to 0.075 MPa, and silica sol with a solid content of 40 wt% was drawn in until the liquid level was 25 cm above the fiber fabric preform. The pressure was maintained for 4 hours. The preform was then removed and placed in an oven at 185°C to dry to constant weight. After cooling, the second impregnated preform was obtained. The preform with secondary impregnation was placed in a firing furnace, and the heating rate was controlled at 80℃ / h to raise the temperature to 355℃ and hold for 4h. The heating rate was then controlled at 120℃ / h to raise the temperature to 455℃ and hold for 3h. Finally, the heating rate was controlled at 150℃ / h to raise the temperature to 805℃ and hold for 4h. After cooling, a quartz fiber preform was obtained.
[0021] 4. Preparation of finished product Quartz fiber blanks are processed into products according to requirements. The products are then vacuum impregnated by drawing a vacuum to -0.098 MPa and holding it for 5 hours. Silica sol with a solid content of 15 wt% is then drawn in until the liquid level is 25 cm above the product. The pressure is maintained for 4 hours. The product is then removed and placed in an oven at 185℃ to dry to constant weight. The vacuum impregnation process is repeated 4 times. After vacuum impregnation, the temperature is raised to 410℃ at a controlled heating rate of 120℃ / h and held for 3 hours. The temperature is then raised to 525℃ at a controlled heating rate of 150℃ / h and held for 3 hours. Finally, the product is cooled to obtain quartz fiber reinforced quartz composite material.
[0022] Example 3 1. Fabric pretreatment Quartz fiber fabric was cleaned with a 10wt% hydrochloric acid solution. After cleaning, deionized water was used to replace the acid radicals. Once the pH of the washing solution was neutral, it was dried at 120℃ to constant weight. After drying, it was pre-fired by heating at a rate of 20℃ / h to 250℃ and holding for 1 hour, heating at a rate of 30℃ / h to 450℃ and holding for 1 hour, heating at a rate of 40℃ / h to 550℃ and holding for 1 hour, and then placing it in a firing furnace. The heating rate was controlled at 50℃ / h to 345℃ and holding for 0.5 hours, the heating rate was controlled at 80℃ / h to 445℃ and holding for 1 hour, and the heating rate was controlled at 120℃ / h to 515℃ and holding for 2 hours. After cooling, quartz fiber braid was obtained. The quartz fiber fabric has an areal density of 305 g / m³. 2 The volume fraction is 42%.
[0023] 2. Centrifugal impregnation Quartz powder and silica sol were mixed at a mass ratio of 1:1.2 and ball-milled for 60 hours at a ball milling speed of 35 r / min and a ball-to-material ratio of 1:2.1 to obtain a slurry with a viscosity of <300 mPa·S. The quartz powder has a particle size of 1200 mesh. The silica sol has a solid content of 10%. Quartz fiber braids were fixed in a centrifuge. Slurry was added to the centrifuge, with the slurry level 20 cm above the quartz fiber braids. The centrifuge speed was adjusted to 350 rpm, and the mixture was centrifuged for 30 minutes. The mixture was then removed and placed in a 180℃ oven to dry for 12 hours. After cooling, the heating rate was controlled at 60℃ / h, and the temperature was raised to 445℃. The temperature was held for 1 hour, and then the heating rate was controlled at 100℃ / h, and the temperature was raised to 660℃. The temperature was held for 0.5 hours, and then the mixture was cooled to obtain a quartz fiber reinforced quartz composite preform.
[0024] 3. Preparation of quartz fiber preforms The quartz fiber reinforced quartz composite preform was placed upright in a vacuum mold and evacuated to -0.085 MPa for 2 hours. Then the pressure was adjusted to -0.015 MPa, and silica sol with a solid content of 45 wt% was drawn in until the liquid level was 20 cm above the quartz fiber reinforced quartz composite preform. The pressure was maintained for 3 hours, and the preform was dried in an oven at 150°C to constant weight. After cooling, a first-impregnation preform was obtained. The first impregnation preform was placed upright in a vacuum mold, and a vacuum of -0.085 MPa was maintained for 3 hours. The pressure was then adjusted to -0.050 MPa, and silica sol with a solid content of 25 wt% was drawn in until the liquid level was 20 cm above the fiber fabric preform. The pressure was maintained for 2 hours. The preform was then removed and placed in an oven at 180°C to dry to constant weight. After cooling, the second impregnation preform was obtained. The preform with secondary impregnation was placed in a firing furnace, and the heating rate was controlled at 50℃ / h to raise the temperature to 345℃ and hold for 1h. The heating rate was then controlled at 80℃ / h to raise the temperature to 445℃ and hold for 1h. Finally, the heating rate was controlled at 120℃ / h to raise the temperature to 795℃ and hold for 2h. After cooling, a quartz fiber preform was obtained.
[0025] 4. Preparation of finished product Quartz fiber blanks are processed into products according to requirements. The products are then vacuum impregnated by drawing a vacuum to -0.085 MPa and holding it for 2 hours. Silica sol with a solid content of 10 wt% is then drawn in until the liquid level is 20 cm above the product. The pressure is maintained for 2 hours. The product is then removed and placed in an oven at 180℃ to dry to constant weight. The vacuum impregnation process is repeated twice. After vacuum impregnation, the temperature is raised to 400℃ at a controlled heating rate of 80℃ / h and held for 1 hour. The temperature is then raised to 515℃ at a controlled heating rate of 100℃ / h and held for 1 hour. Finally, the product is cooled to obtain quartz fiber reinforced quartz composite material.
[0026] The quartz fiber reinforced quartz composite materials prepared in Examples 1-3 were subjected to the following performance tests, and the test results are as follows:
[0027] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0028] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material, characterized in that, This includes fabric pretreatment, centrifugal sizing, preparation of quartz fiber preforms, and preparation of finished products; The fabric pretreatment steps are as follows: the quartz fiber fabric is cleaned with hydrochloric acid solution. After cleaning, it is dried to constant weight and then pre-fired. The temperature is increased to 250-255℃ at a rate of 20-40℃ / h and held for 1-3 hours. The temperature is increased to 450-460℃ at a rate of 30-50℃ / h and held for 1-3 hours. The temperature is increased to 550-560℃ at a rate of 40-60℃ / h and held for 1-3 hours. Then, it is placed in a firing furnace, and the temperature is increased to 345-355℃ at a rate of 50-80℃ / h and held for 0.5-3 hours. The temperature is increased to 445-455℃ at a rate of 80-100℃ / h and held for 1-3 hours. The temperature is increased to 515-525℃ at a rate of 120-150℃ / h and held for 2-4 hours. After cooling, the quartz fiber braid is obtained.
2. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 1, characterized in that, The quartz fiber fabric has an areal density of 305-325 g / m³. 2 Its volume fraction is 42-45%.
3. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 1, characterized in that, The centrifugal impregnation step is as follows: the quartz fiber braid is placed and fixed in a centrifuge, the slurry is added to the centrifuge, the slurry level is 20-25 cm higher than the quartz fiber braid, the centrifuge speed is adjusted to 350-500 rpm, centrifuged for 30-60 minutes, removed and placed in an oven at 180-185℃ to dry for 12-20 hours, after cooling, the heating rate is controlled at 60-90℃ / h, the temperature is raised to 445-455℃, and held for 1-3 hours, the heating rate is raised to 100-150℃ / h, the temperature is raised to 640-660℃, and held for 0.5-2 hours, and then cooled to obtain a quartz fiber reinforced quartz composite preform.
4. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 1, characterized in that, The slurry is prepared by mixing quartz powder and silica sol at a mass ratio of 1:1.2-1.8, ball milling for 60-96 hours at a ball milling speed of 35-45 r / min and a ball-to-powder ratio of 1:2.1-2.3 to obtain a slurry with a viscosity of <300 mPa·S. The quartz powder has a particle size of 1200-1300 mesh; The silica sol has a solid content of 10-15%.
5. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 1, characterized in that, The steps for preparing the quartz fiber preform include: placing the quartz fiber reinforced quartz composite preform upright in a vacuum mold, evacuating to -0.085 to -0.098 MPa and maintaining the vacuum for 2-5 hours, then adjusting the pressure to -0.015 to 0.035 MPa, and drawing in silica sol with a solid content of 45-60 wt% until the liquid level is 20-25 cm above the quartz fiber reinforced quartz composite preform, maintaining the pressure for 3-5 hours, drying in an oven at 150-180℃ to constant weight, and cooling to obtain a one-time impregnation preform.
6. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 5, characterized in that, The step of preparing the quartz fiber preform further includes placing the primary impregnated preform upright in a vacuum mold, evacuating to -0.085 to -0.098 MPa for 3-5 hours, adjusting the pressure to -0.050 to 0.075 MPa, and drawing in silica sol with a solid content of 25-40 wt% until the liquid level is 20-25 cm above the fiber fabric preform, maintaining the pressure for 2-4 hours, removing it and placing it in an oven at 180-185℃ to dry to constant weight, and cooling it to obtain the secondary impregnated preform; The preform with secondary impregnation is placed in a firing furnace. The heating rate is controlled at 50-80℃ / h, and the temperature is raised to 345-355℃. The temperature is held for 1-4 hours. The heating rate is controlled at 80-120℃ / h, and the temperature is raised to 445-455℃. The temperature is held for 1-3 hours. The heating rate is controlled at 120-150℃ / h, and the temperature is raised to 795-805℃. The temperature is held for 2-4 hours. After cooling, a quartz fiber preform is obtained.
7. The method for preparing a needle-stitched structure adapted to fiber-reinforced quartz composite material according to claim 1, characterized in that, The preparation steps are as follows: the quartz fiber blank is processed into a product according to requirements, the product is vacuum impregnated, the vacuum is drawn to -0.085 to -0.098 MPa and held for 2-5 hours, silica sol with a solid content of 10-15 wt% is drawn in until the liquid level is 20-25 cm above the product, the pressure is maintained for 2-4 hours, the product is taken out and placed in an oven at 180-185℃ to dry to constant weight, and then the vacuum impregnation is repeated 2-4 times. After the vacuum impregnation is completed, the temperature is raised to 400-410℃ at a controlled heating rate of 80-120℃ / h and held for 1-3 hours, the temperature is raised to 515-525℃ at a controlled heating rate of 100-150℃ / h and held for 1-3 hours, and then cooled to obtain the quartz fiber reinforced quartz composite material.